Thyroid Papillary Carcinoma Follicular Variant: Which Surgical Approach? - M. Gazi Yıldız; Sedat Aydın; Arif Şanlı; Mustafa Paksoy; Aylin Ege Gül (Haseki Tıp Bülteni)
In general, fine needle aspiration biopsy (FNAB) is insufficient and inadequate in the diagnosis of follicular variant of thyroid papillary carcinoma. Especially in capsulated forms of the carcinoma, diagnostic difficulties are pronounced because of the histopathologic structures. Clinical behaviour of the carcinoma varies from slow progression to aggressive spread. Furthermore, surgical treatment modality is controversial. In this paper, we present six patients who were diagnosed with capsulated follicular variant of thyroid papillary carcinoma in whom fine needle aspiration biopsy results and post operative pathological diagnosis were different. Surgical treatment choice was thyroid lobectomy in one patient due to single nodule, subtotal thyroidectomy in two patients and total thyroidectomy in three patients. According to the postoperative pathology reports, three patients underwent total thyroidectomy. In this study, we emphasized that the follicular variant should be taken into account in patients whose fine needle aspiration biopsy results are not malignant.